Royal jelly protects brain tissue against fluoride-induced damage by activating Bcl-2/NF-?B/caspase-3/caspase-6/Bax and Erk signaling pathways in rats - Aslan, Abdullah; Beyaz, Seda; Gok, Ozlem; Parlak, Gozde; Can, Muhammed Ismail; Agca, Can Ali; Parlak, Akif Evren (Springer Heidelberg, 2023)
This study is aimed at determining whether royal jelly (RJ) which has a powerful antioxidant property prevents fluoride-induced brain tissue damage and exploring whether Bcl-2/NF-kappa B/ and caspase-3/caspase-6/Bax/Erk pathways play a critical role in the neuroprotective effect of RJ. Wistar albino rats were chosen for the study, and they were randomly distributed into six groups: (i) control; (ii) royal jelly; (iii) fluoride-50; (iv) fluoride-100; (v) fluoride-50 + royal jelly; (vi) fluoride-100 + royal jelly. We established fluoride-induced brain tissue damage with 8-week-old male Wistar albino rats by administration of fluoride exposure (either 50 mg/kg or 100 mg/kg bw) through drinking water for 8 weeks. Then, the study duration is for 56 days where the rats were treated with or without RJ (100 mg/kg bw) through oral gavage. The effects of RJ on glutathione (GSH), catalase activity (CAT), and malondialdehyde (MDA) levels were determined via spectrophotometer. Western blot analysis was performed to investigate the effects of royal jelly on the protein expression levels of Bax, caspase-3, caspase-6, Bcl-2, NF-kappa B, COX-2, and Erk. It was also studied the effects of RJ on histopathological alterations in fluoride-induced damage to the rat brain. As a result, the Bcl-2, NF-kappa B, and COX-2 protein expression levels were increased in the fluoride-treated (50 and 100 mg/kg) groups but they were decreased significantly by RJ treatment in the brain tissue. Additionally, the protein expression of caspase-3, caspase-6, Bax, and Erk were decreased in fluoride-treated groups and they were significantly increased by RJ treatment compared to the un-treated rats. Our results suggested that RJ prevented fluoride-induced brain tissue damage through anti-antioxidant activities.
Keywords: Bax; Bcl-2; Brain damage; Caspase-3; 6; Fluoride; Oxidative stress; Royal jelly